2018
DOI: 10.1007/s00253-018-8891-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating molecular and ecological approaches to identify potential polymicrobial pathogens over a shrimp disease progression

Abstract: It is now recognized that some gut diseases attribute to polymicrobial pathogens infections. Thus, traditional isolation of single pathogen from disease subjects could bias the identification of causal agents. To fill this gap, using Illumina sequencing of the bacterial 16S rRNA gene, we explored the dynamics of gut bacterial communities over a shrimp disease progression. The results showed significant differences in the gut bacterial communities between healthy and diseased shrimp. Potential pathogens were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 63 publications
0
31
2
Order By: Relevance
“…In particular, this interplay was disrupted when shrimp disease occurred (Supporting Information Figure S5B). Disease-induced changes in the gut functional composition have been extensively detected in shrimp (Dai et al, 2018a;Xiong et al, 2015a), fish (Li et al, 2017) and humans (Hollister et al, 2015). A possible explanation is that disturbance, for example disease, skews the association between host genetics and its associated microbiota, with consequent dysbiosis in functions (Moya & Ferrer, 2016;Wegner et al, 2013).…”
Section: Disease Decouples Phylogenetic and Functional Association mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, this interplay was disrupted when shrimp disease occurred (Supporting Information Figure S5B). Disease-induced changes in the gut functional composition have been extensively detected in shrimp (Dai et al, 2018a;Xiong et al, 2015a), fish (Li et al, 2017) and humans (Hollister et al, 2015). A possible explanation is that disturbance, for example disease, skews the association between host genetics and its associated microbiota, with consequent dysbiosis in functions (Moya & Ferrer, 2016;Wegner et al, 2013).…”
Section: Disease Decouples Phylogenetic and Functional Association mentioning
confidence: 99%
“…However, there is increasing evidence of strong host filters on the symbiotic microbiota, where hosts of the same species living in different aquatic habitats share similar gut bacterial communities (Rungrassamee et al., ; Schmidt, Smith, Melvin, & Amaralzettler, ; Tzeng et al., ). Recently, it became clear that host diseases could attribute to dysbiosis (shifts in the microbial community that have a negative impact on the host [Petersen & Round, ]) in the gut microbiota (Dai, Yu, Xuan, Zhen, & Xiong, ; Nie, Zhou, Qiao, & Chen, ; Xiong et al., ; Yu, Cao, Dai, Qiu, & Xiong, ). In this regard, a better understanding of the route of transmission or acquisition of gut symbionts is indispensable, because it aids in designing better disease management strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the shrimp IM-disease relationship have identified long lists of implicated microbes that may reflect biomarkers of disease (Xiong et al, 2017;Dai et al, 2018;Hou et al, 2018), without clearly elucidating either the altered microbial functions or the host response against pathogens (Xiong, 2018). In the present study, we identified predictive multigene biomarkers for WFS by combining metagenome and full-length transcriptome data.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, our study showed that the a-diversity of IM was significantly less pronounced in WFS ( Figure 1A), providing more clues to establish that the beta-diversity may be associated with disease. In our previous work (Hou et al, 2018) and other related studies (Xiong et al, 2017;Dai et al, 2018), a series of complicated taxa were found to be associated with WFS by comparing the microbial compositional differences between healthy and diseased shrimp. However, the functional differences between Control and WFS shrimp still remain unclear.…”
Section: Discussionmentioning
confidence: 99%